PENGARUH PENGETAHUAN DAN RELIGIUSITAS TERHADAP MINAT NASABAH CICIL EMAS PADA BANK SYARIAH INDONESIA KCP MUARA BULIAN - Salsa Marlina Putri; El Munawwarah; Alfazri Rahmadani (JOURNAL SAINS STUDENT RESEARCH, 2025)
This thesis research is motivated by the importance of knowledge about gold investment, as it can influence customers’ decisions in selecting appropriate products. Individuals with a good understanding of the benefits and risks of gold investment tend to be more interested in investing. Additionally, religiosity plays a crucial role in investment decisions, especially within the context of Islamic banking. Customers with a high level of religiosity are likely to prefer products that comply with sharia principles and their religious values. The research method used is quantitative with a survey approach. The population of this study consists of gold installment customers in 2024 at Bank Syariah Indonesia KCP Muara Bulian. Using Slovin’s formula, a sample of 95 respondents was determined, with 30 respondents used for a trial test and 65 respondents for the instrument testing. Data collection techniques included literature review, direct observation, and questionnaires. The data obtained were analyzed using multiple linear regression analysis with SPSS version 20. The results revealed that: Knowledge partially influences customers’ interest with a t-count value greater than the t-table (2.835 > 1.998). The second hypothesis found that Religiosity partially influences customers’ interest with a t-count value greater than the t-table (3.071 > 1.998). The third hypothesis, tested with the F-test, showed that Knowledge and Religiosity simultaneously influence customers’ interest with an F-count value greater than the F-table (7.022 > 3.14).